Nursing Perspectives on Sudden Cardiac Arrest After ICU-toWard Transfer in a Patient With ST-Elevation Myocardial Infarction: A Case Study - Nur Hidayati; Gia Ayu Shinta (Universitas Airlangga, 2026)
Introduction: Patients with acute myocardial infarction remain at risk of sudden deterioration after transfer from the intensive care unit to the general ward, highlightingthe importance of strict monitoring, careful transfer-readiness assessment, and vigilantnursing observation to prevent fatal outcomes. Objective: This case study aims to describe the nursing care of a patient with STEMI duringICCU and the transition from the ICCU to the general ward.Case: A 58-year-old woman was admitted to the ICCU after PCI with ST-elevationmyocardial infarction (STEMI) and cardiogenic shock. She had a medical history ofhypertension, diabetes mellitus, and dyslipidemia, with no history of chest pain or smoking.Supporting examinations revealed elevated leukocyte count, troponin I, random bloodglucose, and prothrombin time. The patient also experienced metabolic acidosis andcardiomegaly, while electrocardiography demonstrated inferior ST-segment elevation. Thepatient received oxygen therapy, intravenous fluids, vasoactive support, diuretics,anticoagulants, antiplatelets, statins, and insulin. Conclusions: After four days of treatment in the ICCU, the patient was transferred to the general ward in a stable condition. However, she subsequently developed recurrent chestpain while eating, followed by cardiac arrest, and died despite 30 minutes ofcardiopulmonary resuscitation. This case emphasizes the need for standardized clinicalassessment before transferring patients with acute myocardial infarction from the ICCU tothe general ward. It also highlights the importance of close monitoring during the first 24hours after transfer to ensure early detection of clinical deterioration and to reduce the riskof fatal outcomes.